PELATIHAN PENYUSUNAN BUKU AJAR UNTUK GURU DI SD NEGERI NOGOSARI 06 KECAMATAN RAMBIPUJI - Handayani, Rifati Dina; Lesmono, Albertus Djoko; Supriadi, Bambang (Jurnal Likhitaprajna, 2023)
Teachers are crucial in increasing student interest in learning through books or teaching materials that are attractive, contextual, and interactive. This service activity is carried out considering the needs of the elementary teachers at SD Nogosari 06 Rambipuji district. The problem that arises is the lack of understanding and ability of elementary teachers to establish interactive textbooks. This service activity was conducted for three months, with the substantial covering the introduction of the categories of textbooks and the preparation of textbook drafts. The method used in this activity is using lectures and discussions. The findings indicated that teachers are becoming more aware of the importance of preparing textbooks. The implementation of this activity also received a positive response from the SDN Nogosari 06 Rambipuji District teachers.